2017
DOI: 10.58397/ashkmdc.v22i3.128
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies in women with anxiety and depression during prenatal period

Abstract: Objective: To determine the frequency and association of coping strategies with  different  levels  of  anxiety and depression. Methods: A cross-sectional study was carried out in private hospitals of Karachi, from January to May 2017. Data was collected from pregnant women willing to participate in the study by using non-probability convenient  sampling.  A  questionnaire  was  used  to  gather  socio-demographic  and  obstetric  data after informed consent  from  pregnant  women.  Hospital  anxiety  an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Research has proven that maladaptive coping strategy is a primary cause of "psychological problems" such as "depression," "anxiety," "rapid mood fluctuations, and various other minor and major mental health problems." A study conducted on Pakistani expecting mothers showed that if all maladaptive means are adopted, then it will lead to abnormal behavior since this research concluded a negative association between maladaptive coping and normal human behavior (Rabia et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Research has proven that maladaptive coping strategy is a primary cause of "psychological problems" such as "depression," "anxiety," "rapid mood fluctuations, and various other minor and major mental health problems." A study conducted on Pakistani expecting mothers showed that if all maladaptive means are adopted, then it will lead to abnormal behavior since this research concluded a negative association between maladaptive coping and normal human behavior (Rabia et al, 2017).…”
Section: Introductionmentioning
confidence: 95%